Borrelia carolinensis sp. nov., a novel species of the Borrelia burgdorferi sensu lato complex isolated from rodents and a tick from the south-eastern USA - Rudenko, Nataliia; Golovchenko, Maryna; Grubhoffer, Libor; Oliver, James H (International journal of systematic and evolutionary microbiology, 2011)
A group of 16 isolates with genotypic characteristics different from those of known species of the Borrelia burgdorferi sensu lato complex were cultured from ear biopsies of the rodents Peromyscus gossypinus and Neotoma floridana trapped at five localities in South Carolina, USA, and from the tick Ixodes minor feeding on N. floridana. Multilocus sequence analysis of members of the novel species, involving the 16S rRNA gene, the 5S-23S (rrf-rrl) intergenic spacer region and the flagellin, ospA and p66 genes, was conducted and published previously and was used to clarify the taxonomic status of the novel group of B. burgdorferi sensu lato isolates. Phylogenetic analysis based on concatenated sequences of the five analysed genomic loci showed that the 16 isolates clustered together but separately from other species in the B. burgdorferi sensu lato complex. The analysed group therefore represents a novel species, formally described here as Borrelia carolinensis sp. nov., with the type strain SCW-22(T) (=ATCC BAA-1773(T) =DSM 22119(T)).
Keywords: mezerníky ribozomální DNA; Ixodes; polymorfismus délky restrikčních fragmentů; klíště; Borrelia burgdorferi Group; Animals; molekulární sekvence - údaje; DNA bakterií; DNA, Bacterial; Molecular Sequence Data; Polymorphism, Restriction Fragment Length; Multilocus Sequence Typing; South Carolina; Jižní Karolína; RNA ribozomální 16S; Bacterial Typing Techniques; Sigmodontinae; Borrelia burgdorferi komplex; multilokusová sekvenční typizace; Sequence Analysis, DNA; flagelin; RNA, Ribosomal, 16S; Flagellin; DNA, Ribosomal Spacer; zvířata; fylogeneze; sekvenční analýza DNA; Phylogeny; techniky typizace bakterií